Comparison of acute responses to four different hypertrophy-oriented resistance training methodologies - Sabido, R.; Penaranda, M.; Hernández-Davó, J. L. (European Journal of Human Movement, 2016)
Muscle hypertrophy has been associated with both athletic performance and quality of life. Although hypertrophy-oriented resistance training methodologies are very popular, it is still unclear the different physiological and perceptual responses to some of these methodologies. The aim of this study was to compare the acute effects of four different hypertrophy-oriented resistance training methodologies. During four weeks, seventeen participants with experience in resistance training performed a once-a-week resistance training session, differing the methodology (traditional, pyramid, agonist supersets and agonist paired supersets). Acute responses to the different training sessions were measured via lactate concentration, peak velocity losses, rating of perceived exertion, and number of assisted repetitions. Both lactate concentration and rating of perceived exertion showed that the agonist paired supersets caused greater values compared with either the traditional or the pyramid methodologies. Although all of the methodologies led to significant decreases in peak velocity, these decreases were not different between methodologies. The results of the present study highlight the agonist paired supersets as being the most stressed methodology when talking about acute fatigue responses to a single training session. Further research is required to evaluate if these large acute fatigue effects could lead to greater muscle hypertrophy following a training intervention.